PERSPEKTIF GENDER DALAM PEMBERDAYAAN KELOMPOK WANITA TANI ARIMBI MELALUI PROGRAM CORPORATE SOCIAL RESPONSIBILITY DI ADISUCIPTO YOGYAKARTA - Tiana Yulianti; Ramadhanita Mustika Sari (Smart Education, 2025)
Abstract: This study aims to examine the synergy between PT Pertamina DPPU Adisucipto and the Arimbi Women Farmers Group (KWT) in implementing the Corporate Social Responsibility (CSR) program. The program includes the provision of plant seeds, fish, farming equipment, as well as training and mentoring for KWT Arimbi members in Maguwoharjo Village, Sleman. By applying the triple bottom line principles (economic, social, and environmental), the program seeks to empower women, improve daily economic needs, enhance local food production, and strengthen the relationship between the company and the community. This research employs a literature approach by collecting databases from books, journals, articles, and documents from related institutions. Economic challenges are complex and require the involvement of all parties simultaneously and in a coordinated manner to realize the vision of community economic independence. The results show improvements in economic self-sufficiency, prevention of stunting, and business diversification. Continuous evaluation ensures the program's effectiveness and positive impact on the community. Active community participation and shifts in traditional gender roles act as catalysts for innovation, creating a more inclusive and sustainable.Keywords: Gender Perspective, Empowerment, Economy, Arimbi Women Farmers,Â Group (KWT), CSR Abstrak: Penelitian ini bertujuan untuk mengkaji sinergi antara PT Pertamina DPPU Adisucipto dan Kelompok Wanita Tani (KWT) Arimbi dalam pelaksanaan program Corporate Social Responsibility (CSR). Program ini mencakup pemberian bibit tanaman, ikan, peralatan budidaya, serta pelatihan dan pendampingan bagi anggota KWT Arimbi di Desa Maguwoharjo, Sleman. Dengan menerapkan prinsip triple bottom line (ekonomi, sosial, dan lingkungan), program ini bertujuan untuk memberdayakan perempuan, meningkatkan Penelitian ini menggunakan pendekatan literature dengan pengumpulan database buku, jurnal, artikel, dan dokumen dari lembaga terkait. Agar mampu terpenuhi kebutuhan ekonomi sehari-hari. Masalah perekonomian merupakan masalah yang sangat konpleks yang membutuhkan keterlibatan semua pihak bersamaan dan terkodinasi supaya cita-cita kemandirian ekonomi masyarakat terealisasikan. produksi pangan lokal, dan memperkuat hubungan antara perusahaan dan komunitas. Hasilnya menunjukkan peningkatan kemandirian ekonomi, pencegahan stunting, dan diversifikasi usaha. Evaluasi berkelanjutan memastikan efektivitas dan dampak positif program bagi masyarakat. Partisipasi aktif masyarakat dan perubahan peran gender tradisional menjadi katalisator inovasi, menciptakan struktur sosial yang lebih inklusif dan berkelanjutan.Kata kunci: Perspektif Gender, Pemberdayaan, Ekonomi, KWT Arimbi, CSR.